2020
DOI: 10.3390/ijerph17134874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DNA Damage and Oxidative Stress in Human Bronchial Epithelial Cells Exposed to PM2.5 from Beijing, China, in Winter

Abstract: Epidemiological studies have corroborated that respiratory diseases, including lung cancer, are related to fine particulate matter (<2.5 μm) (PM2.5) exposure. The toxic responses of PM2.5 are greatly influenced by the source of PM2.5. However, the effects of PM2.5 from Beijing on bronchial genotoxicity are scarce. In the present study, PM2.5 from Beijing was sampled and applied in vitro to investigate its genotoxicity and the mechanisms behind it. Human bronchial epithelial cells 16HBE were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 54 publications
(59 reference statements)
0
24
0
Order By: Relevance
“…[15][16][17] PM 2.5 exposure is also associated with increased risk of chronic obstructive pulmonary disease, heart disease, asthma, stroke, preterm labor, and death, [18][19][20][21][22][23] and is known to promote oxidative stress. 24 Similarly, lung, breast, and prostate incidence has been linked to nitrogen dioxide and other measures of traffic exposure, [25][26][27] and cancer mortality has been linked to traffic proximity. 28 Thus, exposure to these air toxins results in a 16% higher cancer risk among individuals living in Black-dominant areas than those in European American-dominant areas (P , .01).…”
Section: Pollution Exposurementioning
confidence: 99%
“…[15][16][17] PM 2.5 exposure is also associated with increased risk of chronic obstructive pulmonary disease, heart disease, asthma, stroke, preterm labor, and death, [18][19][20][21][22][23] and is known to promote oxidative stress. 24 Similarly, lung, breast, and prostate incidence has been linked to nitrogen dioxide and other measures of traffic exposure, [25][26][27] and cancer mortality has been linked to traffic proximity. 28 Thus, exposure to these air toxins results in a 16% higher cancer risk among individuals living in Black-dominant areas than those in European American-dominant areas (P , .01).…”
Section: Pollution Exposurementioning
confidence: 99%
“…However, in vitro studies suggest that relatively short exposure to PM2.5 may induce cellular changes and inflammation (ref. [33,34]).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported new aspects of PMrelated oxidative stress in the lung tissue. A study by Niu et al (43), using human bronchial epithelial (HBE) cells, showed increased levels of ROS, malondialdehyde, and cellular heme oxygenase and decreased levels of GSH, after exposure to PM 2.5 , reflecting the occurrence of oxidative stress in a dose-dependent manner. Quantitative analysis indicated that PM 2.5 caused a significant increase in malondialdehyde in a dose-dependent manner, while GSH was greatly reduced after exposure (P<0.05).…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%